First, expand the terms on the right side of the equation by multiplying each term within the parenthesis by the term outside the parenthesis:
#-5y + 16 = color(red)(-3)(y - 6)#
#-5y + 16 = (color(red)(-3) xx y) - (color(red)(-3) xx 6)#
#-5y + 16 = -3y - (-18)#
#-5y + 16 = -3y + 18#
Now, subtract #color(red)(16)# and add #color(blue)(3y)# to both sides of the equation to isolate the #y# term while keeping the equation balanced:
#color(blue)(3y) - 5y + 16 - color(red)(16) = color(blue)(3y) - 3y + 18 - color(red)(16)#
#(color(blue)(3) - 5)y + 0 = 0 + 2#
#-2y = 2#
Now, divide each side of the equation by #color(red)(-2)# to solve for #y# while keeping the equation balanced:
#(-2y)/color(red)(-2) = 2/color(red)(-2)#
#(color(red)(cancel(color(black)(-2)))y)/cancel(color(red)(-2)) = -1#
#y = -1#